An approach for visualizing the spatial metabolome of an entire plant root system inspired by the Swiss‐rolling technique. (14th May 2019) - Veličković, Dušan; Chu, Rosalie K.; Myers, Gabriel L.; Ahkami, Amir H.; Anderton, Christopher R.
Abstract: The spatial configuration and morphology of roots are commonly monitored for a better understanding of plant health and development. However, this approach provides minimal details about the biochemistry regulating the observable traits. Therefore, the ability to metabolically map the entire root structure would be of major value. Here, we developed a sample preparation approach that enables imaging of the entire root within a restricted space (width of microscope slide), which was influenced by the Swiss‐rolling technique. We were able to image and confidently identify molecules along the entire root structure from rolled‐root tissue sections using multiple spatially resolved mass spectrometry approaches.